Metaphor Analysis in “Death By A Thousand Cuts” and “False God” Song Lyrics by Taylor Swift - Olivia Apriliani Muslimah; Afni Apriliyanti Devita (ReALL - Research on Applied Linguistics and Literature, 2023)
Taylor Swift is an American singer who released the album Lover in 2019. In the album, there are songs titled "Death by Thousand Cuts" and "False God" whose lyrics tell about her love story. In this study, the researcher tries to reveal the meaning of the lyrics of the two songs with metaphors. Metaphors are often used in songwriting to implicitly convey meaning. Taylor Swift, who has always been known for her incredible lyrics, is no exception. The method used in this study is descriptive qualitative with a metaphorical approach according to Ullman and Leech. The result obtained is that the two songs have the same number of metaphors. The song “Death by Thousand Cuts” has 6 metaphors out of 16 lines of lyrics, and the song “False God” has 6 metaphors out of 15 lines of lyrics. Then the metaphor with the highest number according to the data analysis is the type of metaphor from concrete to abstract with a total of 5. From the results of the analysis of the two songs, it proves that the role of metaphor in a song can help listeners understand meaning and feelings in depth. By using concrete to abstract metaphors, Taylor Swift tries to tell a clear story to listeners through her songs.